ANALISIS PENERAPAN SISTEM WEB PELITA TERHADAP PROSES AUDIT LAPORAN KEUANGAN KANTOR AKUNTAN PUBLIK Z - Dinda Rokhmatun Nazila; Binti Shofiatul Jannah (Politeknik Negeri Malang, 2026)
This study analyzes the use of the Pelita Web System in the financial statement audit process at Public Accounting Firm (KAP) Z. The research is motivated by the risk of falsification of Independent Auditor Reports (LAI) by illegal firms, which undermines the authenticity of audit documents and public trust. To address this issue, Pelita Web was introduced as a digital platform to enhance transparency, accountability, and integrity in the public accounting profession. Using a qualitative case study approach, data were collected through interviews and direct observations with auditors. The findings reveal that Pelita Web System improves the efficiency of validation, prevents falsification, and supports audit activities through a structured and user-friendly workflow. Overall, Pelita Web demonstrates its role as a strategic tool in strengthening audit credibility and maintaining the reliability of financial reports.